Re-testing Wagner’s Law: Structural breaks and disaggregated data for South Africa - Mlilo, Mthokozisi; Netshikulwe, Matamela (Journal of Economics and Behavioral Studies, 2017)
Direction of causality between government expenditure and output growth is pertinent for a developing country since a sizeable volume of economic resources is in the hands of the public sector. This paper investigates the Wagner’s law in South Africa over the post-apartheid era, 1994-2015. This paper is unique to present studies since it uses disaggregated government expenditure and controls for structural breaks. The Granger non-causality test of Toda & Yamamoto, a superior technique compared to conventional Granger causality testing, is employed and this paper finds no support for Wagner’s law. However, there is causality running from total government and education expenditures to output. This finding is in line with the Keynesian framework. It is recommended in the paper that the government should take an active role in promoting output growth through increases in education expenditures in particular.